Drip and ship for mechanical thrombectomy within the Neurovascular Network of Southwest Bavaria. (4th February 2020) - Feil, Katharina; Rémi, Jan; Küpper, Clemens; Herzberg, Moriz; Dorn, Franziska; Kunz, Wolfgang G.; Rotkopf, Lukas T.; Heinrich, Johanna; Müller, Katharina; Laub, Christoph; Levin, Johannes; Hüttemann, Katrin; et al.
Abstract : Objective: To determine feasibility and safety of stroke care organization within our Neurovascular Network of Southwest Bavaria (NEVAS) in a rural area with distances of up to 100 kilometers, we compared patients who underwent mechanical thrombectomy (MT) in large vessel occlusion admitted directly to our center (direct to center [DTC]) to patients who were transferred for MT via NEVAS (drip and ship [DS]). Methods: This is a retrospective analysis of prospectively collected data of all MT patients between January 2015 and May 2018. Successful recanalization was defined as a thrombolysis in cerebral infarction score of 2b-3. Symptomatic intracerebral hemorrhage (sICH) was defined according to European Cooperative Acute Stroke Study 3. Modified Rankin Scale (mRS) score of 0–2 at 3 months indicated good outcome. Results: MT was performed in 410 patients: 221 DTC and 189 DS. Median NIH Stroke Scale (NIHSS) score was 16 and premorbid mRS score was 0. Thrombolysis was applied in 62.2% with the same time from symptom onset in both groups (94.5 vs 95 minutes). Successful recanalization (79.3% vs 77.8%) and NIHSS score reduction from admission to discharge (16–7 vs 17–6) were comparable. Time delay from onset to revascularization was 96 minutes in DS (212 vs 308 minutes, p = 0.001). At follow-up, DTC patients had a trend to better outcome (33.5% vs 24.3%, p = 0.056). Neither sICH (6.3% vs 5.9%, p = 0.840) nor mortality (31.2% vs 34.4%, p = 0.387) differed between the groups. Conclusion: DS patients benefit from MT without relevant safety concerns, but with a trend to unfavorable outcome compared to DTC patients. These results suggest that DS is suitable to provide MT in rural areas where DTC is not possible.